1997
DOI: 10.1200/jco.1997.15.4.1465
|View full text |Cite
|
Sign up to set email alerts
|

Prostate-specific antigen failure despite pathologically organ-confined and margin-negative prostate cancer: the basis for an adjuvant therapy trial.

Abstract: Prostate cancer patients with pathologically organ-confined and margin-negative disease and a preoperative PSA level greater than 10 ng/mL or a pathologic Gleason score > or = 7 have significant decrements in short-term PSA-failure-free survival. Therefore, these patients should be considered for adjuvant therapy in the setting of a phase III clinical trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…7 Conversely, margin negative, extracapsular extension negative patients may have relapse rates as high as 40% at three years if other prognostic factors are unfavourable. 33 In fact, survival curves for margin positive patients are similar to those for extracapsular extension positive, margin negative patients. 3 5 6 Although in some studies margin status has been more important than extraprostatic extension of carcinoma in the prediction of recurrence, 1 2 13 other studies have found limited impact on survival adjusted for extraprostatic extension and seminal vesicle invasion, 5 and this is reflected in the AJCC staging system.…”
Section: Discussionmentioning
confidence: 89%
“…7 Conversely, margin negative, extracapsular extension negative patients may have relapse rates as high as 40% at three years if other prognostic factors are unfavourable. 33 In fact, survival curves for margin positive patients are similar to those for extracapsular extension positive, margin negative patients. 3 5 6 Although in some studies margin status has been more important than extraprostatic extension of carcinoma in the prediction of recurrence, 1 2 13 other studies have found limited impact on survival adjusted for extraprostatic extension and seminal vesicle invasion, 5 and this is reflected in the AJCC staging system.…”
Section: Discussionmentioning
confidence: 89%
“…2 Identifying patients in whom primary curative therapy is likely to fail would be helpful for selecting those best suited for clinical trials of early systemic intervention, sparing men the morbidity associated with ineffective local therapy and/or predicting patient outcome. 2,3 To improve the preoperative prediction of patient stage groups have evaluated additional information available in initial prostate needle biopsies. Factors such as quantitative nuclear grade, 4 total percent cancer in biopsy cores (PosBx), 5 a combination of percent positive biopsy (greater than 50%), and the number of positive cores (NoPosBx) 6 -9 have been found to improve the prediction of pathological stage.…”
mentioning
confidence: 99%
“…Therefore, it is important to define successful adjuvant and salvage treatment strategies for postoperative patients who are at high risk for clinical failure. At present, there are no studies that clearly demonstrate a survival benefit for any type of post-prostatectomy therapy [3,5].…”
Section: Introductionmentioning
confidence: 99%
“…These patients are at high risk for subsequent biochemical and clinical recurrence. Even for patients who successfully undergo RP with negative pelvic lymph nodes and negative surgical margins, approximately 15%-40% of these patients will develop a biochemical recurrence within 3 years of RP depending on the pretreatment PSA (PSA > 10) and pathologic Gleason score (Gleason score >6) [3]. Overall, Pound et al [4] at Johns Hopkins have stated that "between 27% and 53% of men undergoing radical prostatectomy will have a detectable PSA elevation within 10 years following surgery."…”
Section: Introductionmentioning
confidence: 99%